Experimental study on long-distance SPAD-based VLC systems. (August 2019) - Xue, Jingshu; Zhu, Yijun; Wang, Chao; Zhang, Dongfang; Mu, Yu
Abstract: Long-distance visible light communication (VLC) based on single photon avalanche diode (SPAD) can supplement the existing wireless communication mechanism in many senarios. Although there are many researches on VLC in recent years, the experiments on long-distance VLC are relatively scarce. In this paper, we use the experimental method to study the long-distance VLC, so as to apply it to two new application scenarios — VLC between buildings and in mountainous areas. A system model is established for both of the scenarios. Based on the model, a low energy consumption device for long-distance VLC is completed to realize the long-distance transmission of voice and data. At the end of the paper, we simulate the performance of the proposed system. The results indicate that the system is feasible to realize the duplexing voice and data transmission within the range of 2 km when the data rate is below 200 kbps.